HUBUNGAN TINGKAT PENGETAHUAN GIZI DAN SIKAP DENGAN KEBIASAAN SARAPAN PADA MAHASISWA - Ainun Najla; Erike Septa Prautami; Rini Mutahar; Faradina Aghadiati (CV. Adiba Aisha Amira, 2025)
Breakfast is essential for supporting energy for thinking, working, and performing physical activities optimally, especially for university students. This study aims to analyze the relationship between the level of nutritional knowledge and attitudes with breakfast habits among students at the Faculty of Public Health Sriwijaya University. This research applied a cross-sectional study design with 161 respondents. Data were collected using a questionnaires and analyzed using the chi-square test. The result of this study showed that 59% of students had a good level of nutritional knowledge, 32.9% moderate, and 8.1% low. Furthermore, 90.7% of students had a positive attitude, while 9.3% negative. Regarding breakfast habits, 49.1% of students had good habits and 50.9% had poor habits. Statistical analysis indicated a significant relationship between nutritional knowledge (p=0.027; PR = 3.558; 95% CI = 0.981–12.898) and attitude (p=0.018; PR = 1.669; 95% CI = 1.231–2.262) with breakfast habits among students at the Faculty of Public Health Sriwijaya University. A higher level of nutritional knowledge and more positsive attitudes toward breakfast are associated with better breakfast habits among students. It is recommended that students pay more attention to their breakfast habits and continue to increase their knowledge about healthy breakfasts.